2021
DOI: 10.2174/1874364102115010217
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Optometrists Regarding Low Vision Services in Saudi Arabia

Abstract: Purpose: To address the human resources challenge for the provision of low vision services in Saudi Arabia, this study sought to investigate the knowledge, attitudes, and practices of optometrists in Saudi Arabia regarding low vision services. The knowledge and attitudes to low vision services can influence the provision of low vision services by optometrists. Methods: A prospective cross-sectional survey of optometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
2
Order By: Relevance
“…Based on the results, the distribution of respondents by region and gender was similar to that obtained from the Saudi Commission for Health Specialties in 2021. The obtained response rate of the current study was 9.06%, which is higher than the rates reported in previous studies that targeted optometrists and other healthcare professionals in Saudi Arabia at 2.6% and 1.6%, respectively [23][24] . With respect to the clinical tests used to examine schoolaged children with myopia, there was a slightly higher preference for cycloplegic refraction measures (59% and 54%, respectively).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Based on the results, the distribution of respondents by region and gender was similar to that obtained from the Saudi Commission for Health Specialties in 2021. The obtained response rate of the current study was 9.06%, which is higher than the rates reported in previous studies that targeted optometrists and other healthcare professionals in Saudi Arabia at 2.6% and 1.6%, respectively [23][24] . With respect to the clinical tests used to examine schoolaged children with myopia, there was a slightly higher preference for cycloplegic refraction measures (59% and 54%, respectively).…”
Section: Discussioncontrasting
confidence: 72%
“…The proportion of respondents who completed the survey did not significantly differ from the population of practicing optometrists in Saudi Arabia based on sex (χ 2 =0.44, P=0.5) and region (χ 2 =2.05, P=0.36). The percentage of respondents in this study was greater than that reported in previous studies that targeted optometrists and other healthcare practitioners in Saudi Arabia [23][24] .…”
Section: Resultscontrasting
confidence: 61%
“…4 In severe cases, some participants preferred microscopes for magnification while performing near tasks and the prescription for near vision decreased significantly from +19.50 to +10.23 D when correcting for near vision; this improvement can lead to noticeable changes in magnification (Table 3). In addition, various lens types, refractive indices, coatings 27,28 and prism designs can also be incorporated to address visual limitations, such as photophobia, glare and reduced contrast sensitivity simultaneously with a single pair of eyeglasses (Table 4). 10,11…”
Section: Eyeglasses and Additional Olvasmentioning
confidence: 99%